An integrated approach to improve maternal and perinatal outcomes in rural Guatemala: A stepped‐wedge cluster randomized trial. Issue 1 (27th July 2020) - Kestler, Edgar; Ambrosio, Guillermo; Hemming, Karla; Hughes, James P.; Matute, Jorge; Moreno, Mario; Madriz, Solange; Walker, Dilys
Abstract: Objective: To evaluate the impact of an intervention package on maternal and newborn health indicators. Methods: A randomized stepped‐wedge non‐blind trial was conducted across six subdistricts within two districts in Guatemala from January 2014 to January 2017. Data on outcomes were collected on all deliveries in all 33 health centers. The intervention package included distribution of promotional materials encouraging health center delivery; education for traditional birth attendants about the importance of health center delivery; and provider capacity building using simulation training. Main outcomes were number of health center deliveries, maternal morbidity, and perinatal morbidity and mortality. Results: Overall, there were 24 412 deliveries. Health center deliveries per 1000 live births showed an overall increase, although after adjustment for secular trends and clustering, the relative risk for the treatment effect was not statistically significant (aRR, 1.04; 95% confidence interval [CI], 0.97–1.11, P =0.242). Although not statistically significant, maternal morbidity (aRR, 0.78; 95% CI, 0.60–1.02; P =0.068) and perinatal morbidity (aRR, 0.84; 95% CI, 0.68–1.05; P =0.133) showed a tendency toward a decrease. Conclusion: The present study represents one of the few randomized evaluations of an integrated approach to improve birth outcomes in a low‐income setting. ClinicalTrials.gov: NCT0315107. Abstract : A stepped‐wedge intervention to increase health center deliveries while building the capacity of birth attendants was found to be feasible and may improve obstetric indicators.